EVALUASI PELAKSANAAN SASARAN KESELAMATAN PASIEN TERHADAP PERLINDUNGAN PASIEN RAWAT INAP PASCA OPERASI DI RUMAH SAKIT BHAKTI KARTINI TAHUN 2023 - Adjrina Dawina Putri (2024)
Patient safety is an important issue in providing health services. Patient Safety Incidents, in the form of death or injury, can arise if patient safety is not implemented according to the applicable standards. One of the standards used in Indonesia is the Patient Safety Goals (PSGs). This research aimed to evaluate the implementation of PSGs for the protection of post operative hospitalized patients at Bhakti Kartini Hospital in 2023. This research used qualitative methods with descriptive study design. The results shows that the implementation of 5 out of 6 PSGs has been very well. The efforts to protect patients from the risk of infection and the risk of post operative complications have been successful. However, there is a lack of consistency in protecting the patients from the injury due to fall risks. Constraints on material resources, such as an unstable internet network, AC that is not cold enough or noisy, and emergency trolleys that locked, indirectly affect the implementation of PSGs. Researcher recommends Bhakti Kartini Hospital to form a special team to monitor patients who have undergone further assessments to reduce the risk of falls and to provide a program and checklist sheet to ensure material resources work well.